(untitled) (Proceedings of Voronezh State University. Series: Geology, 2019)
the main industrial value of the Boulder ore cluster are gold and silver. Traditionally, platinum mineralization was not associated with the Au-Ag formation. For the first time, platinum mineralization was noted in the Mayskoye field of the East Sikhote-Alin volcanic belt of the Au-Ag formation, where platinum minerals were discovered. Then native Pt was recorded on the Au-Ag ore occurrence Milogradovskoye. Later, at the same facility, aggregate gravity-enriched platinum grains were obtained, by self-assembly during the finest grinding and processing using special technology. The article presents the da- ta of x-ray spectral microanalysis of ore minerals from the heavy fraction of sample pro-logs and polished sections of ore-bearing rocks. The minerals of sulfides of lead, iron, zinc, and silver were studied. Some of the samples were analyzed by atomic absorption method. The results obtained give reason to reconsider the ore potential of the studied object for its platinum content.